PENGOLAHAN LIMBAH RUMAH TANGGA DALAM RANGKA PROGRAM ZERO WASTE DI SEKTOR 6 CITARUM HARUM KABUPATEN BANDUNG - Wardhiani, Wini Fetia; Rimelke Rahmadea Febryane; Mohammad Bayu Anggara (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2025)
The Citarum Harum Program is a government initiative to rehabilitate and preserve the Citarum River, which is known as one of the dirtiest rivers in the world. One of the important strategies in this program is the application of the zero waste principle at the household level, especially in Sector 6 of Bandung Regency. This study examines efforts to process household waste as part of implementing the zero waste program in the area. The research method used is a qualitative-descriptive approach through field observations, interviews with residents and stakeholders, and documentation studies. The results of the study indicate that public education, provision of waste sorting facilities, and collaboration between the government, community, and residents are key factors in the success of waste processing. Processing organic waste through composting and utilizing inorganic waste into goods of economic value has been proven to reduce the volume of waste disposed of at the landfill. And for residual waste, it is used as paving blocks that have an economic selling value. Although there are still challenges such as low community participation evenly and limited facilities, the efforts made show a positive direction towards sustainable waste management. These findings are expected to be a reference for the development of community-based waste management policies in other areas.